Role Play for Fostering Young Learner's Soft Skill in Speaking English - Jayanti, Lukitaning Nur (Vivid: Journal of Language and Literature, 2022)
This paper is about exploring what and how soft skills can be gained from using a role-playing game while teaching a speaking skill to children. This study is conducted by analyzing and observing data result from other studies related to this research objective. The subject of this research is a young learner average eight to ten years old student of elementary school. The role play referred to in this research is a simple role-play such as acting and playing pretend that young learners can understand without complicated components. They will perform a role play without set dialogue, only with a scenario idea as they will use their ability to conduct the role play. This study was conducted because of the importance of a soft skill that impacts children's ability in using language. This study found that there are better communication skills, analytical and problem-solving skills, decision-making judgment, and boost learner self-confidence in using English as a second language. Communication skills and self-confidence are developing because there is an interaction between speakers in the context of role-play scenarios. Children tend to imprint a lesson that they experience themselves, consequently making them remember their mistake when they speak English in an attempt to have a conversation in communication. Thence this makes students learn from past mistakes and become more fluent in speaking English as a second language that does not sound stiff as a robot, unlike when they only learn from the textbook. Roleplay is fostering children's analytical thinking, problem-solving, and decision-making skill because role-play gave them a context of how to apply language in a real-life situation. The student will try to think in a logical order and to speak what they want, consequently stimulating their thinking ability in a good way.